Problems of early large panel structures in Poland - Wojciech Górski (Acta Scientiarum Polonorum. Architectura)
The first buildings composed of prefabricated elements appeared in Poland in the 1960s and large housing estates were constructed in this technology already in the 1970s. Rising housing demands had impact on the rapid development of factory-produced structures and the creation of a series of technologies, such as Wk-70, Wrocław Large Panel (WWP) or the Szczecin system (Sz-s). Over the years, several defects of this technology have surfaced on different levels of building erection or exploitation. Part of these flaws was related with the aesthetics of the structures, without influence in their construction, whereas others required fast actions for maintenance of safety to the residents. The paper presents an overview of the most important Polish systems of large panel structures, as well as the sources of defects and flaws that may appear in buildings constructed in this technology.